Investigation of the Investment Activity of the Eurasian Economic Union - Artur Arturovich Gibadullin (Управленческое консультирование)
The article presents the prerequisites for the formation of international organizations based on mechanisms for the unification of national industries and states. The Russian Federation is currently an active participant in economic and political alliances, and often initiates the creation of supranational alliances in the territory of the former Soviet Union. To date, several interstate organizations are functioning, the most successful is the Eurasian Economic Union, within which common markets for goods and services have been formed, a free flow of labor and capital is provided, and strategic tasks have been set for convergence of national industrial production into a common supranational complex. In this connection, the study devoted to the issues of investment activity in the member states of the Eurasian Economic Union is relevant. The analysis showed that the investment in fixed capital per capita in Belarus, Kazakhstan and Russia is on average the same, while in Armenia and Kyrgyzstan it is four times less. According to sources of financing, investments are formed, mainly, at the expense of own funds of enterprises and organizations, budget appropriations and borrowed funds of credit institutions. At the end of the article, mechanisms of attraction at the supranational level are proposed.